Effect of reaction conditions on electron induced graft copolymerization of styrene onto poly(ethylene-co-tetrafluoroethylene) films: Kinetics study - Rohani, Rosiah; Nasef, Mohamed Mahmoud; Saidi, Hamdani; Mohd Dahlan, Khairul Zaman (Elsevier B.V., 2007)
Graft copolymerization of styrene onto electron preirradiated poly(ethylene-co-tetrafluoroethylene) (ETFE) films was investigated. Effects of reaction conditions: monomer concentration, irradiation dose, temperature, film thickness and storage time on the grafting yield (Y%) were studied. The initial rate of grafting was found to be heavily dependent on the monomer concentration and the irradiation dose and can be represented by the following equation: dGo/dt = k[Mo]2.0[D]0.75. The overall activation energies for graft copolymerization were calculated to be 36.9 and 12.5 kJ/mol below and above 50 Â°C, respectively. The initial rate of grafting was found to decrease with the increase in the film thickness. The trapped radicals in the irradiated ETFE films were found to be highly effective in initiating grafting reaction up to 240 days when stored under -60 Â°C. Graft copolymerization in the present study essentially depends on the ability of the monomers to diffuse through the base film and the amount of the trapped radicals.